The Role of Islamic Boarding Schools in Increasing Digital Financial Literacy in Indonesia - Khotibul Umam; Yunadi Yunadi; Alkauzer Alkauzer; Try Itsnawati; Ulfatul Hasanah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
Digital financial services in Indonesia have developed significantly, and even several Islamic boarding schools have implemented digital financial services for various types of transactions. Islamic boarding schools, one of Indonesia's oldest educational institutions, certainly have an important meaning in increasing financial literacy in Indonesia. The application of digital financial services in Islamic boarding schools is a strategic step in increasing financial literacy from an early age, especially for students, so that they form good habits in managing their finances in the future, such as knowing the meaning of money, having a habit of saving, and prioritizing needs over wants. Digital financial services in Islamic boarding schools can increase financial literacy for students and their parents because students are taught to manage their finances wisely by prioritizing their needs over desires. In addition, parents and Islamic boarding schools can instil the values of a good financial literacy philosophy while monitoring students' consumption levels through these digital financial services that they can access from their mobile phones